Sartori and Italian politics: joy and sorrow. Issue 3 (2nd September 2017) - Pasquino, Gianfranco; Valbruzzi, Marco
ABSTRACT: This article explores Giovanni Sartori's contributions to the analysis and understanding of Italian politics. Sartori never studied and analysed the case of Italy in 'splendid' isolation from other cases. Rather he was at pains to place Italy within a broad and empirically grounded comparative perspective. On the basis of his approach, Sartori repeatedly intervened in the Italian public debate to suggest his own proposals for the improvement of the performance of the political system and, more in general, of the democratic regime. In this article, our discussion of Sartori's approach and contributions to the field of Italian politics will follow three highly intertwined threads. First, we will deal with the contribution provided by Giovanni Sartori to the analysis and definition of the somewhat elusive Italian party system. Second, we will explore his relevant contribution to the study of electoral systems throughout the world, especially taking into account both the specificities and the oddities of the Italian electoral 'laboratory'. Third, we will investigate the increasing tensions, especially, but not exclusively, provoked by Berlusconi's enduring influence on Italian politics, between democratic principles, on the one hand, and the doctrine of liberalism and constitutionalism, on the other. The concluding section will evaluate Sartori's contributions to the advancement/improvement of political science in Italy, in particular as a discipline capable of acquiring and producing knowledge that can and should be applied.